Immunological Response against Breast Lineage Cells Transfected with Human Papillomavirus (HPV) - Daffany Luana Santos; Bianca de França São Marcos; Georon Ferreira de Sousa; Leonardo Carvalho de Oliveira Cruz; Bárbara Rafaela da Silva Barros; Mariane Cajuba de Britto Lira Nogueira; Talita Helena de Araújo Oliveira; Anna Jessica Duarte Silva; Vanessa Emanuelle Pereira Santos; Cristiane Moutinho Lagos de Melo; Antonio Carlos de Freitas (Viruses, 2024)
Breast cancer is the most common neoplasm worldwide. Viral infections are involved with carcinogenesis, especially those caused by oncogenic Human Papillomavirus (HPV) genotypes. Despite the detection of HPV in breast carcinomas, the virus’s activity against this type of cancer remains controversial. HPV infection promotes remodeling of the host’s immune response, resulting in an immunosuppressive profile. This study assessed the individual role of HPV oncogenes in the cell line MDA-MB-231 transfected with the E5, E6, and E7 oncogenes and co-cultured with peripheral blood mononuclear cells. Immunophenotyping was conducted to evaluate immune system modulation. There was an increase in CD4+ T cell numbers when compared with non-transfected and transfected MDA-MB-231, especially in the Treg profile. Pro-inflammatory intracellular cytokines, such as IFN-γ, TNF-α, and IL-17, were impaired by transfected cells, and a decrease in the cytolytic activity of the CD8+ and CD56+ lymphocytes was observed in the presence of HPV oncogenes, mainly with E6 and E7. The E6 and E7 oncogenes decrease monocyte expression, activating the expected M1 profile. In the monocytes found, a pro-inflammatory role was observed according to the cytokines released in the supernatant. In conclusion, the MDA-MB-231 cell lineage transfected with HPV oncogenes can downregulate the number and function of lymphocytes and monocytes.